Noise Exposure-Induced Functional Anatomical Changes: Impact on Superoxide Dismutase, Tumor Necrosis Factor-Alpha, and Adiponectin - Suka Astini, Dewa Ayu Agung Alit; Luh Gde Evayanti; Sri Ratna Dewi (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Environmental noise is a non-auditory stressor that can trigger inflammatory and oxidative responses in the body. Continuous noise exposure is associated with increased production of pro-inflammatory cytokines and reactive oxygen species (ROS). This can disrupt the body's cellular balance. This study aimed to determine the effects of chronic noise exposure on serum superoxide dismutase (SOD), tumor necrosis factor-alpha (TNF-α), and adiponectin levels in wistar rats. Methods: This study used a laboratory based experimental design, involving twenty-four adult male Wistar rats. The rats were randomly divided into two groups: a control group and a treatment group. The treatment group was exposed to 95 dB noise for four hours daily for 14 consecutive days, while the control group received no exposure. SOD, TNF-α, and adiponectin levels were determined using ELISA. The independent t-test was used for statistical analysis. Results and Discussion: TNF-α was significantly higher (p < 0.05) and adiponectin was significantly lower (p < 0.05) in the treatment group than in the control group. SOD levels did not differ significantly across groups (p > 0.05). Noise exposure causes metabolic and inflammatory disruptions, as evidenced by the rise in TNF-α and fall in adiponectin, but the SOD levels remain unchanged, suggesting a limited antioxidant response. Conclusion: An inflammatory response and decreased adiponectin were caused by noise exposure at 95 dB for 14 days, suggesting a possible risk of metabolic dysfunction. Nonetheless, the stability of SOD levels indicates that enzymatic antioxidant action is maintained in these circumstances.